Peningkatan Literasi Menulis Teks Deskripsi Melalui E-LKPD Scan to Adventure - Wiguna, Arya Chandra; Abidin, Yunus; Muna Aljamaliah, S. Nailul (Buletin Literasi Budaya Sekolah, 2024)
This research concerns the development of E-LKPD scan to adventure to improving the descriptive text writing skills of fourth-grade elementary school students. Development research design utilizes D&D type 1 which focuses on product design, development, and evaluation. The results of the feasibility test and field test are presented on a scale of 1-4 where categories 1 (strongly disagree), 2 (disagree), 3 (agree), 4 (strongly agree). The results of material validation obtained a mode score of 3 which had the "agree" category with the appropriateness of the material content and learning aspects, and the expert assessment of teaching materials obtained a mode score of 3 which had the "agree" category with the feasibility aspects of the E-LKPD components, the quality of the E-LKPD. LKPD and E-LKPD display. Meanwhile, from the field test results, the client's response to the use of the E-LKPD scan to adventure that was developed obtained a mode score of 4 with the category "strongly agree" in the aspects of the appropriateness of the material content and quality of the E-LKPD. From users' responses to the use of E-LKPD, they obtained a mode score of 4 with the category "strongly agree" on the material and quality aspects of E-LKPD.